Adrenomedullin is a therapeutic target in colorectal cancer. Issue 9 (7th November 2013) - Wang, Liangjing; Gala, Manish; Yamamoto, Masayoshi; Pino, Maria S.; Kikuchi, Hirotoshi; Shue, Daniel S.; Shirasawa, Senji; Austin, Thomas R.; Lynch, Maureen P.; Rueda, Bo R.; Zukerberg, Lawrence R.; Chung, Daniel C.
<x xml:space="preserve">Abstract</x> The KRAS oncogene influences angiogenesis, metastasis and chemoresistance in colorectal cancers (CRCs), and these processes are all enhanced in hypoxic conditions. To define functional activities of mutant KRAS in a hypoxic microenvironment, we first performed cDNA microarray experiments in isogenic DKs5 and DKO3 colon cancer cell lines that differ only by their expression of mutant KRAS (K‐rasD13). Adrenomedullin (ADM) was identified as one of the most significantly upregulated genes in DKs5 cells that express the KRAS oncogene in hypoxia (3.2‐fold, p = 1.47 × 10−5). Ectopic expression of mutant KRAS (K‐rasV12) in Caco‐2 cells (K‐rasWT) induced ADM, whereas selective knockdown of mutant KRAS alleles (K‐rasD13 or K‐rasV12) in HCT116, DLD1 and SW480 colon cancer cells suppressed the expression of ADM in hypoxia. Knockdown of ADM in colon tumor xenografts blocked angiogenesis and stimulated apoptosis, resulting in tumor suppression. Furthermore, ADM also regulated colon cancer cell invasion in vitro. Among 56 patients with CRC, significantly higher expression levels of ADM were observed in samples harboring a KRAS mutation. Collectively, ADM is a new target of oncogenic KRAS in the setting of hypoxia. This observation suggests that therapeutic targets may differ depending upon the specific tumor microenvironment.